Շիրվանի խանությունը XVIII դարի երկրորդ կեսին — XIX դարի սկզբին - Մահբուբե Սեդիղի (ՀՀ ԳԱԱ հրատ.)
Shirvan khanate was one of the muslim khanates formed in Transcaucasia in the second half of 18th century. On major part the representatives of the family of Serkers held the post of the khans of Shirvan in their hands. In 1768-1774 Shirvan khanate was subordinated to Fathali khan of Quba. From the end of 18th century Shirvan khanate like the other khanates became-the object of struggle between Russian Empire and Qajar Iran.
Keywords: History